“My Honor is My Life”: Sturm Brightblade of the Dragonlance Saga and Middle English Arthurian Knighthood - Sell, Carl B. (Romanica Silesiana, 2021)
Arthuriana has a long history of adaptation and appropriation in medieval and contemporary works, and the tradition of such textual borrowing and reworking continues in contemporary “genre” novels, particularly those that invoke associations with knights, honor, and codes of chivalry. One such example are the novels and short stories of the Dragonlance setting. Sturm Brightblade is positioned as a knight who adheres to a code of honor and is given Arthurian character traits, narrative arcs, and a backstory by the various authors that have fleshed out his history. The texts in the Dragonlance setting knowingly use appropriated elements from Middle English Arthurian works and assign them to Sturm Brightblade to give him proper positioning as a knight that would fit in with Arthur’s legendary Round Table.